Effect of Evaporator and Condenser Temperatures on the Performance of Adsorption Desalination Cooling Cycle. (August 2015) - Youssef, P.G.; AL-Dadah, R.K.; Mahmoud, S.M.; Dakkama, H.J.; Elsayed, A.
Abstract: As world population is growing the need for fresh water is increasing. Many technologies have been investigated for seawater desalination but each one has its own drawbacks. Desalination process with adsorption technology has gained interest in the last few years due to its ability to use waste heat sources leading to minimal energy requirements and reduced CO2 emissions. This work mathematically investigates the effect of evaporator and condenser temperatures on the adsorption cycle performance for the production of potable water and cooling effect using silica-gel as the adsorbent material. It was found that as condenser temperature decreases, more water is produced and higher specific cooling capacity was achieved. Moreover, as evaporator temperature increases, similar improvements in water production and cooling were achieved. Results showed that for 10 o C condenser water temperature and 30 o C evaporator inlet water temperature, potable water production of 10 m 3 /tonne silica-gel/day and specific cooling capacity (SCC) of 77 Rton/tonne silica-gel were achieved highlighting the potential of this cycle.